Enhanced dengue vaccine virus replication and neutralizing antibody responses in immune primed rhesus macaques - Michael K. McCracken; Caitlin H. Kuklis; Chandrika B. Kannadka; David A. Barvir; Mark A. Sanborn; Adam T. Waickman; Hayden C. Siegfried; Kaitlin A. Victor; Kristin L. Hatch; Rafael De La Barrera; Shannon D. Walls; Wiriya Rutvisuttinunt; et al. (npj Vaccines, 2021)
Abstract Antibody-dependent enhancement (ADE) is suspected to influence dengue virus (DENV) infection, but the role ADE plays in vaccination strategies incorporating live attenuated virus components is less clear. Using a heterologous prime-boost strategy in rhesus macaques, we examine the effect of priming with DENV purified inactivated vaccines (PIVs) on a tetravalent live attenuated vaccine (LAV). Sera exhibited low-level neutralizing antibodies (NAb) post PIV priming, yet moderate to high in vitro ADE activity. Following LAV administration, the PIV primed groups exhibited DENV-2 LAV peak viremias up to 1,176-fold higher than the mock primed group, and peak viremia correlated with in vitro ADE. Furthermore, PIV primed groups had more balanced and higher DENV-1–4 NAb seroconversion and titers than the mock primed group following LAV administration. These results have implications for the development of effective DENV vaccine prime-boost strategies and for our understanding of the role played by ADE in modulating DENV replication.